The Antistaphylococcal Lysin, CF-301, Activates Key Host Factors in Human Blood To Potentiate Methicillin-Resistant Staphylococcus aureus Bacteriolysis - Indiani, Chiara (Antimicrob Agents Chemother, 2019)
Bacteriophage-derived lysins are cell-wall-hydrolytic enzymes that represent a potential new class of antibacterial therapeutics in development to address burgeoning antimicrobial resistance. CF-301, the lead compound in this class, is in clinical development as an adjunctive treatment to potentially improve clinical cure rates of Staphylococcus aureus bacteremia and infective endocarditis (IE) when used in addition to antibiotics. In order to profile the activity of CF-301 in a clinically relevant milieu, we assessed its in vitro activity in human blood versus in a conventional testing medium (cation-adjusted Mueller-Hinton broth [caMHB]). CF-301 exhibited substantially greater potency (32 to ≥100-fold) in human blood versus caMHB in three standard microbiologic testing formats (e.g., broth dilution MICs, checkerboard synergy, and time-kill assays). We demonstrated that CF-301 acted synergistically with two key human blood factors, human serum lysozyme (HuLYZ) and human serum albumin (HSA), which normally have no nascent antistaphylococcal activity, against a prototypic methicillin-resistant S. aureus (MRSA) strain (MW2). Similar in vitro enhancement of CF-301 activity was also observed in rabbit, horse, and dog (but not rat or mouse) blood. Two well-established MRSA IE models in rabbit and rat were used to validate these findings in vivo by demonstrating comparable synergistic efficacy with standard-of-care anti-MRSA antibiotics at >100-fold lower lysin doses in the rabbit than in the rat model. The unique properties of CF-301 that enable bactericidal potentiation of antimicrobial activity via activation of “latent” host factors in human blood may have important therapeutic implications for durable improvements in clinical outcomes of serious antibiotic-resistant staphylococcal infections.